SOSIALISASI TEKNOLOGI AUGMENTED REALITY DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA LINGKUP PENGAJARAN YANG TERINTEGRASI - Aryani, Diah; Suharti, Dwi Sloria; Noviandi, Noviandi; Ariessanti, Hani Dewi (Universal Raharja Community (URNITY Journal), 2024)
Because of its emphasis on superimposing virtual information on top of real environments, augmented reality (AR) technology in education has emerged as a cutting-edge and promising field in both research and practice. This sets learning in a different context from traditional learning and opens up a whole new creative realm for learning.. The gap between teaching methods and the technological environment is increasing as a result of students' disinterest and low motivation when using traditional teaching approaches as well as teachers' reluctance to implement learning with technology. The lack of knowledge and ability of teachers at SDN Larangan 5, Tangerang City in the use and use of integrated technology in classroom teaching is still limited, especially for Augmented Reality (AR) technology, so boredom and lack of variety in the disclosure of their teaching materials often occur, which has an impact on learning outcomes. which is not optimal. This community service activity aims to achieve knowledge transfer by socializing learning content by utilizing Augmented Reality (AR) technology using a smartphone or tablet which will later be used to see and observe objects from the markers that have been provided. This activity uses the Community-Based Participatory Action Research (CBPAR) method with three core stages of the CBPAR action cycle, namely: planning, implementation and evaluation. And the results of the analysis of this activity state that there has been an increase in knowledge and interest regarding the use of technology, especially Augmented Reality (AR) technology which is included in learning activities with analysis results of 50%. Keywords: Augmented Reality, Community Based Participatory Action Research (CBPAR), learning content